Application of Two Sex Markers by Nested PCR for Gender Determination - Jonathan Jun-Yong Lim; Mohd Fadhli Khamis; Nur Haslindawaty Binti Abd Rashid (Institute of Medico-legal Publications Pvt Ltd, 2021)
Sex determination is one of the basic components in victim identification. There are many available methods,namely forensic anthropology method and conventional DNA typing method. In this study, nested PCRtechnique was employed in sex typing of burnt teeth through amelogenin (AMEL) and sex-determiningregion Y (SRY) markers. In this study, 17 teeth samples were burnt at temperatures that ranged from 100°Cto 500°C for 2 min - 10 min. The whole tooth was used for DNA extraction by phenol-chloroform method.Accurate sex determination was achieved in 13 samples by both AMEL and SRY markers. The SRY markerachieved higher sensitivity as compared to AMEL marker. The sensitivity of both markers was improvedconsequent to nested PCR. Factors such as degraded DNA materials and the presence of tooth caries greatlyaffect sex typing results. Results showed that nested PCR proved to be a good method to amplify highlydegraded DNA material as it greatly increased the DNA copy, and thus increased the possibility of sextyping.